Bromomethyl Silicate: A Robust Methylene Transfer Reagent for Radical‐Polar Crossover Cyclopropanation of Alkenes. Issue 11 (5th March 2020) - Luo, Wenping; Fang, Yewen; Zhang, Li; Xu, Tianhang; Liu, Yongjun; Li, Yan; Jin, Xiaoping; Bao, Jiakan; Wu, Xiaodong; Zhang, Zongyong
Abstract : A general protocol for visible‐light‐induced cyclopropanation of alkenes was developed with bromomethyl silicate as a methylene transfer reagent, offering a robust tool for accessing highly valuable cyclopropanes. In addition to α‐aryl or methyl‐substituted Michael acceptors and styrene derivatives, the unactivated 1, 1‐dialkyl ethylenes were also shown to be viable substrates. Apart from realizing the cyclopropanation of terminal alkenes, the methyl transfer reaction has been further demonstrated to be amenable to the internal olefins. The photocatalytic cyclopropanation of 1, 3‐bis(1‐arylethenyl)benzenes was also achieved, giving polycyclopropane derivatives in excellent yields. With late‐stage cyclopropanation as the key strategy, the synthetic utility of this transformation was also demonstrated by the total synthesis of LG100268. Abstract : A new bifunctional C1 synthon: With bromomethyl silicate as a CH2 source, visible‐light‐induced cyclopropanation has been demonstrated to be amenable to the alkenes including Michael acceptors, styrene derivatives, and unactivated 1, 1‐dialkyl ethylenes. In addition to the broad substrate scope, this radical‐polar crossover process is also characterized by its redox‐neutral process, mild conditions, and good functional‐group compatibility.